Effectiveness and influencing factors of online education for caregivers of patients with eating disorders during COVID‐19 pandemic in China. (27th August 2020) - Guo, Lei; Wu, Mengting; Zhu, Zhuoying; Zhang, Lei; Peng, Sufang; Li, Wei; Chen, Han; Fernández‐Aranda, Fernando; Chen, Jue
Abstract: Objective: The goals were twofold: To estimate the depression and anxiety levels among caregivers of patients with eating disorders (ED) in China during the COVID‐19 pandemic when compared with a control group, and to assess whether an online education program was effective in decreasing the anxiety and depression of the caregivers of patients with ED, and associated factors. Method: Caregivers of patients with ED ( n = 254) and a comparison group of non‐ED caregivers ( N = 254) were recruited at baseline. Additionally, caregivers of patients with ED were invited into a free 4‐week online education program, with an additional online group as support. Depression and anxiety levels were assessed at baseline and after the intervention. Results: Caregivers of patients with ED showed significantly higher levels of depression and anxiety than the comparison group of non‐ED caregivers. The online education program showed no significant effect on decreasing depression and anxiety levels of caregivers of patients with ED overall. Caregivers who had older loved ones and not living with them were more likely to decrease their depression levels. Caregivers of patients with longer illness duration were less likely to decrease their anxiety levels. Discussion: These results showed that caregivers of ED patients suffered more serious psychological distress during the pandemic. A more structured and intensive online intervention with a limited number of participants might be required to address caregivers' distress in post‐COVID‐19 China.